The role of cross-sectional imaging of the extracranial and intracranial vasculature in embolic stroke of undetermined source - Baradaran, Hediyeh; Kamel, Hooman; Gupta, Ajay (Frontiers in Neurology, 2022)
Despite an extensive workup, nearly one third of ischemic strokes are defined as Embolic Stroke of Undetermined Source (ESUS), indicating that no clear etiologic cause has been identified. Since large vessel atherosclerotic disease is a major cause of ischemic stroke, we focus on imaging of large vessel atherosclerosis to identify further sources of potential emboli which may be contributing to ESUS. For a stroke to be considered ESUS, both the extracranial and intracranial vessels must have less than 50% stenosis. Given the recent paradigm shift in our understanding of the role of plaque vulnerability in ischemic stroke risk, we evaluate the role of imaging specific high-risk extracranial plaque features in non-stenosing plaque and their potential contributions to ESUS. Further, intracranial vessel-wall MR is another potential tool to identify non-stenosing atherosclerotic plaques which may also contribute to ESUS. In this review, we discuss the role of cross-sectional imaging of the extracranial and intracranial arteries and how imaging may potentially uncover high risk plaque features which may be contributing to ischemic strokes.